Critical transmission sectors for provincial food-water nexus in China. (10th January 2021) - Li, Ke; Feng, Cuiyang; Liang, Yuhan; Qi, Jianchuan; Li, Yumeng; Li, Hui; Liang, Sai; Yang, Zhifeng
Abstract: Food and water resources are closely interconnected through economic supply chains. Existing studies have identified critical sectors as either direct water users or food consumers indirectly driving upstream water uses. However, sectors acting as intermediate transmission centres in the virtual water network driven by final food demand are overlooked. Production efficiency improvement of these critical transmission sectors (i.e., using less upstream inputs to produce unitary output) could indirectly reduce water uses of the whole supply chains. Taking China as the case, this study identifies critical transmission sectors for food-water nexus at the provincial level, based on an environmentally-extended multi-regional input-output model and the concept of betweenness. Results show that the agricultural products sectors in Shandong, Heilongjiang, and Hubei are the top three transmission sectors. They transmit 4.6, 4.1, and 3.0 billion m 3 of embodied water resources, respectively. Some important transmission sectors, such as the cotton in Xinjiang and chemical industry in Jiangsu, cannot be identified by production-based and consumption-based methods. Results also highlight the necessity of strengthening inter-regional and inter-sectoral cooperation, because partial critical transmission sectors are not located in the demand provinces. Betweenness-based results can provide additional hotspots for developing sector-oriented policies for the synergistic management of food and water resources. Highlights: Critical transmission sectors for provincial food-water nexus are identified. Agricultural products and chemical industry are critical transmission sectors. Spatial distribution of critical transmission sectors is uncovered. The productivity of critical transmission sectors should be improved. Strengthening inter-regional and inter-sectoral cooperation is essential.